A Data-Driven Service Creation Approach for End-Users - Zhongyi Zhai; Bo Cheng; Yue Tian; Junliang Chen; Lingzhong Zhao; Meng Niu (IEEE Access, 2016)
Spurred by Web technologies and service computing paradigm, more and more Web services have been delivered via standardized interfaces on the Internet. Mashup is exactly an enabling technology for end-users to combine these services into applications. However, there are some issues of end-user service development with mashup techniques. It not only requires users that develop application logics equipped with more or less programming skills, but also lacks a lightweight mashup model and systematic development approach in the existing mashup tools. To address these issues, we propose a data-driven service creation approach to facilitate application development and deployment. In the approach, we propose the service data model (SDM) for adaptation of heterogeneous Web services, the service relation model (SRM) for representation and refinement of data interaction between services, and the service process graph (SPG) for describing business logics of mashup applications. We develop an IFrame implementation for SDM that can facilitate service providers to wrap heterogeneous Web services in a unified way and display a visual element for the service. Meanwhile, we implement a pipeline as an intuitive form of SRM that can be used by end-users to develop business logic more effectively. To adapt the dynamic application scenarios, we also construct an event-driven execution mechanism for SPG. A lightweight service creation environment is then implemented to support end-users to develop applications in a simulative way, and a corresponding development methodology is introduced for this tool. Finally, the end-user evaluation and performance evaluation are conducted to evaluate our platform.